INCREASING LEG MUSCLE EXPOSURE POWER WITH ALTERNATE LEG BOUND IN SEPAK TAKRAW PLAYERS - Febriani, Yelva; Adenikheir, Annisa; Yanti, Noptri (PHYSIO MOVE JOURNAL, 2024)
Explosive power in sports is a component that must be possessed in some sports, because this is related to the results of all work instructions carried out by individuals and groups. Explosive power can be increased with regular and systematic training. Alternative Leg Bound training functions to increase muscle explosive power so that athletes have high explosive power in carrying out their activities. This study aims to determine the effect of giving Alternative Leg Bound on the explosive power of muscle spasms in sepak takraw players in Kamang in 2023. The sample collection technique used purposive sampling. This research was carried out with a youth population of 20 people, with a sample of 10 people. Muscle explosive power is measured using a vertical jump. The results of research on giving Alternative Leg Bound showed that the average explosive power of muscle spasms before the intervention was 32.30 after giving the intervention to 42.00 and the effect test showed p= 0.000, meaning that there was an increase in muscle explosive power in sepak takraw players with the administration of Alternate Leg Bound. Keywords : Alternate Leg Bound, Muscular Explosive Power, Sepak Takraw